The Production Rates Of Pakchong Elephant Grass Based On Different Urea Fertilizer Dosage Levels - Cahyani, Febriyanti Regina; Prihantoro, Iwan; Toharmat, Toto (Faculty of Animal Science, Universitas Gadjah Mada, 2024)
Pakchong elephant grass (PEG) is a super fodder with significant nutritional content and high production levels. The purpose of this research is to quantify the growth and yield of PEG through nitrogen fertilizer engineering with different dosages and repeated fertilization methods. A completely randomized design (CRD) was employed in the investigation, with 4 different levels of urea dosage (100; 200; 300; and 400 N kg/ha). And 10 replicates. ANOVA was used to evaluate the data, and Duncan's Multiple Range Test was then used to determine whether the treatments were substantially different (P<0.05). The findings demonstrated that the addition of nitrogen fertilizer at dosages of 200–400 N kg/ha was better compared to 100 N kg/ha at the end of maintenance (8 weeks after planting) for the quantity of leaves, leaf length, the height of plant, production of both fresh and dry biomass of PEG. There were no significant effect (P>0.05) in nitrogen fertilizer levels at the end of maintenance (8 weeks after planting) for leaf width, leaf chlorophyll content, stem sugar content, quantity of tillers, and the leaf-to-stem ratio of PEG. The research's conclusion indicates that adding nitrogen fertilizer up to 400 N kg/ha is generally safe and feasible for the growth and production of PEG. A nitrogen fertilizer dosage of 200 N kg/ha is optimal to meet PEG's growth and production needs.